Rebecca's Natural Food : sparking small business and local community involvement in Charlottesville - Mulloth, Bala, (SAGE business cases., 2023)
In this case study, readers will analyze the growth, evolution, and innovation of Rebecca's Natural Food, a socially minded grocer that provides locally sourced, sustainable, and healthy products for the public. Founded in 1987 by Norman Dill, the organization's mission was to orchestrate a movement championing the need for healthy, sustainable, anti-hormone, fresh local food. To do so, the organization took a unique social entrepreneurial approach. By engaging closely with the local community and building partnerships with a range of small businesses, the organization has been able to set itself apart as a business that meets exceptional standards. The case will investigate the team's social motivations and shared values that contribute to the organization's goals and vision. Further, the case will discuss the various strategic decisions and dilemmas the organization faces as they seek to maximize impact in the years ahead. Finally, the case will offer some of the lessons learned and potential new directions Rebecca's Natural Food has proposed to take.